Akulturasi Budaya Minangkabau dan Ajaran Tarekat Naqsabandiyah di Surau Kaciak Pasca Perang Paderi - Sagita Ramadhani; Nurul Hidayati; Silviana Silviana; Fariz Alfadilah Arentha (Medan Resource Center, 2022)
This article aims to identify the acculturation of Minangkabau culture with the teachings of the Naqsabandiyah tariqa in Bonjol District, Pasaman Regency after the Paderi War. The purpose of this article is to find out the influence of the teachings of the Naqsabandiyah Order on Padgambling, and animist practices that are contrary to Islam. then replaced with traditions that conform to Islamic sharia or Islamic sharia. This article focuses on developments related to the customs or traditions of indigenous peoples who have been replaced by scholars who practice one of the orders, the Naqsabandiyah tariqa. This article uses historical methods, namely heuristics, verification, interpretation, and historiography. through literature review, especially the study of Surau Haji Mohammad Said Bonjol manuscripts and their correlation with Surau Kaciak and other studies relevant to previous research. The results of this study concluded that the impact of the Paderi war on the habits of the Bonjol people began to shift from animism to the practice of Islamic sharia or Sharia which was brought by the priest community to all levels of society.